Risk Factor Associated with Carotid Intima-Media Thickness inPatients with Systemic Lupus Erythematosus - Made Dyah Vismita Indramila Duarsa (Indonesian Rheumatology Associantion, 2025)
Background: Cardiovascular complications, including atherosclerosis, arethe highest causes of mortality in systemic lupus erythematosus (SLE)patients. The carotid artery intima-media thickness (cIMT) can effectivelyindicate the condition of atherosclerosis in patients. This study wasconducted to determine the associated risk factors for cIMT in patientswith SLE. Methods: This research was conducted as a cross-sectionalstudy at Prof. I.G.N.G. Ngoerah Hospital, Denpasar. From January 2023to June 2023, all SLE patients aged 18-55 for men and 18-65 for women,without infections, cancer, asthma, stage 5 chronic kidney disease, stroke,coronary heart disease, peripheral artery disease, or smoking history, wereincluded. Measurement of cIMT was performed using Dopplerultrasonography. Statistical analysis was conducted using descriptivestatistics and Fisher exact test to assess the association between variables.Results: 52 patients (51 women and 1 man) met the inclusion criteria wereincluded. The mean age was 33.67 ± 10.51 years, the duration of SLE bythe time of diagnose was 50.37 ± 40.39 months, and the disease activityscored by MEX SLEDAI was 2.58 ± 3.24. Moreover, the bivariate analysisshowed a significant association between hypertension and cIMT in SLEpatients (p = 0.001) with an Odd Ratio (OR) of 28.77. The age at diagnosiswas also found to be significantly associated independently with cIMT (p =0.003, OR = 14.93). This is associated with dysregulation of lectin -likeoxidized-LDL (ox-LDL) receptor-1 (LOX-1), leading to an increased risk ofatherosclerotic plaque formation. Conclusion: There is a notableassociation between the occurrence of hypertension and age at diagnosisto the elevated cIMT in SLE patients.